The glucocorticoid receptor gene (NR3C1) is linked to and associated with polycystic ovarian syndrome in Italian families - Shumail Syed; Claudia Gragnoli (BMC, 2024)
Abstract Objectives Components of the hypothalamic-pituitary axis (HPA) pathway are potential mediators of the genetic risk of polycystic ovarian syndrome (PCOS). Impaired glucocorticoid receptor (NR3C1) expression and function may underlie impaired HPA-axis cortisol activity, thereby also contributing to the increased adrenal cortisol and androgen production present in women with PCOS. In this study, we aimed to identify whether NR3C1 is linked or in linkage disequilibrium (LD), that is, linkage joint to association, with PCOS in Italian peninsular families. Method In 212 Italian families with type 2 diabetes (T2D) from the Italian peninsula, previously recruited for a T2D study and phenotyped for PCOS, we used microarray to genotype 25 variants in the NR3C1 gene. We analyzed the 25 NR3C1 variants by Pseudomarker parametric linkage and LD analysis. Results We found the novel implication in PCOS risk of two intronic variants located within the NR3C1 gene (rs10482672 and rs11749561), thereby extending the phenotypic implication related to impaired glucocorticoid receptor. Conclusions To the best of our knowledge, this is the first study to report NR3C1 as a risk gene in PCOS.